Strategi Peningkatan Pelayanan Publik: Studi Kasus di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Maluku Tengah - Sabandar, Petronela; Madubun, Jusuf; Sahetapy, Petronela (MAN 4 Kota Pekanbaru, 2026)
Improving public service quality remains a critical priority for government institutions. This study examines the effectiveness of service improvement strategies at the Investment and One-Stop Integrated Service Office of Central Maluku Regency using an input–process–output framework. A quantitative descriptive design with a census approach was applied, involving all employees as respondents. Data were collected through structured questionnaires and document analysis and analyzed using descriptive statistics and index scoring. The results indicate that the overall effectiveness of service improvement strategies is in the high category, with mean scores of 4.21 for input, 4.18 for process, and 4.25 for output dimensions. The findings reveal improvements in responsiveness, accountability, efficiency, and service accessibility. Key supporting factors include standardized procedures, staff competence, inter-unit coordination, and the integration of digital and manual service mechanisms. This study provides empirical evidence that structured and adaptive management strategies enhance public service performance and offers a practical model for replication in regional government institutions.